Konjac-mulberry leaf compound powder alleviates OVA-induced allergic rhinitis in BALB/c mice - Yiyun Zhang; Jinxing Wang; Qi Zhang; Liling Deng; Siyao Miao; Geng Zhong (Food Science and Human Wellness)
According to the proportion of 1:1, konjac flour and mulberry leaf powder are compounded into a kind of dietary fiber source (KMCP). It is found to be good for anti-inflammation. However, its precise anti-allergic rhinitis effect and mechanism remain unknown. In our work, the effect of KMCP on allergic rhinitis (AR) induced by ovalbumin (OVA) was investigated. We found that the number of nasal rubbing and sneezing, the eosinophil (EOS) count in the nasal mucosa, and the serum levels of histamine (HIS), OVA-specific immunoglobulin E (OVA-sIgE) and interleukin-4 (IL-4) were decreased, and the histopathological changes of nasal mucosa were inhibited. Additionally, the experiments further proved that the KMCP treatment could exert substantial effects on short-chain fatty acids (SCFAs) metabolism in the cecum as well. Overall findings suggest that KMCP could suppress the inflammatory response in AR mice, and serve as a novel curative therapeutic for AR without side effects.